"Arctic Circle and Fur Industry" parade float, Golden Potlatch, July 17, 1912 - University of Washington Libraries. Special Collections Division. (1912)
PH Coll 794.152 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number